Psychometric properties of the EQ-5D-5L compared with EQ-5D-3L in cancer patients in Iran - Moradi, Nasrin; Poder, Thomas G.; Safari, Hossein; Mojahedian, Mohammad M.; Ameri, Hosein (Frontiers in Oncology, 2022)
Background and Objective: Psychometric evidence to support the validity and reliability of the EQ-5D in cancer patients is limited. This study aimed to test the validity and reliability of the EQ-5D-5L (5L) in comparison with EQ-5D-3L (3L) in cancer patients. Methods: Data of 646 cancer patients were collected through consecutive sampling method. The data were gathered using the 3L, 5L, and QLQ-C30 instruments. The 3L and 5L were compared in terms of ceiling effect, inconsistency, discriminatory power, convergent and known-groups validity, relative efficiency, reliability, and agreement. Results: Compared with the 3L, ceiling effect decreased by 27.86%. Absolute and relative informativity improved by 45.93% and 22.92% in the 5L, respectively. All convergent validity coefficients with 5L were stronger than with 3L. Both 3L and 5L demonstrated good known-groups validity, and the relative efficiency was higher for 5L in 4 out of 7 patients' characteristics. The two instruments showed low overall inconsistency (1.45%) and 92.57% of the differences of observations between the 3L and 5L were within the 95% limit of agreement. The ICC for 3L and 5L indexes were 0.88 and 0.85, respectively, and kappa coefficients in the 3L dimensions (range=0.66-0.92) were higher than the 5L(range=0.64-0.79). Conclusions: The 5L demonstrated to be better than the 3L in terms of ceiling effect, inconsistency, discriminatory power, convergent validity, relative efficiency.